How does participating in a deliberative citizens panel on healthcare priority setting influence the views of participants?. Issue 2 (February 2020) - Reckers-Droog, Vivian; Jansen, Maarten; Bijlmakers, Leon; Baltussen, Rob; Brouwer, Werner; van Exel, Job
Highlights: We examined how deliberation changed a panel's views on healthcare priority setting. Participants' views before and after the panel were to a large extent similar. Concerns for equal access, patients' need, and treatment benefits remained stable. Deliberation increased participants' support for prioritisation in healthcare. Participates became more considerate of costs and a cost-effectiveness criterion. Abstract: A deliberative citizens panel was held to obtain insight into criteria considered relevant for healthcare priority setting in the Netherlands. Our aim was to examine whether and how panel participation influenced participants' views on this topic. Participants (n = 24) deliberated on eight reimbursement cases in September and October, 2017. Using Q methodology, we identified three distinct viewpoints before (T0 ) and after (T1 ) panel participation. At T0, viewpoint 1 emphasised that access to healthcare is a right and that prioritisation should be based solely on patients' needs. Viewpoint 2 acknowledged scarcity of resources and emphasised the importance of treatment-related health gains. Viewpoint 3 focused on helping those in need, favouring younger patients, patients with a family, and treating diseases that heavily burden the families of patients. At T1, viewpoint 1 had become less opposed to prioritisation and more considerate of costs. Viewpoint 2 supported out-of-pocket payments more strongly. A new viewpoint 3 emerged that emphasised the importance of cost-effectiveness and that prioritisation should consider patient characteristics, such as their age. Participants' views partly remained stable, specifically regarding equal access and prioritisation based on need and health gains. Notable changes concerned increased support for prioritisation, consideration of costs, and cost-effectiveness. Further research into the effects of deliberative methods is required to better understand how they may contribute to the legitimacy of and public support for allocation decisions in healthcare.